Parámetros ambientales y pesqueros de un lago somero de La Pampa, luego de una mortandad masiva de Odontesthes bonariensis - Del Ponti, O. (2014)
The Bajo Giuliani Lagoon (36 ° 42 ‘20’’ S, 64 ° 16 ‘ 02 ‘’ W) is located south of the city of Santa Rosa, La Pampa, which was stocked with fish during the late 90’s. In this hypertrophic shallow lake, major environmental changes caused mass mortalities of silverside Odontesthes bonariensis, the last one occurred in 2010. In order to know the current state of the environment, in April 2013 surface water samples were collected, several points were georeferenced and major morphometric parameters were estimated. Fish were captured by trawls and gillnets. The lake has an area of 965 ha with an average depth of 2.31 meters, hyposaline, hard and sodium chlorinated water. Captured register 549 specimens of O. bonariensis and 437 of Jenynsia multidentata, showing a low diversity. The captured silverside ranged from 75 to 343 mm standard length and from 4 to 568 grams. The catch per unit effort in number and biomass was 519 fishes/ night and 99.2 kilos / night respectively, and the trophy size (PSD) was 41.6 6 %. The results indicate that PSD was 16% lower than those recorded before mortality in October 2009. Also, CPUE in number and CPUE in weight obtained were lower than that date. Nevertheless, several index showed better current body conditions.